Judicial independence and state-business relations: the case of Taiwan's ordinary courts. Issue 6 (19th September 2017) - Ma, David K.
ABSTRACT: The question of how ordinary courts in new and emerging democracies may gain judicial independence remains an understudied subject compared to its constitutional court counterpart. Through a case study of Taiwan, this article adopts and expands upon the concept of power diffusion from the extant literature, arguing that the growing power of Taiwan's private corporate sector led the dominant political party Kuomintang (KMT) to grant independence to the ordinary courts as a means to check against this threat, because the excessive rent-seeking and corruption brought about by these empowered corporations were threatening the nation's successful economic model and its rule of law. Also, due to the corporate sector's growing influence on the ruling party itself, the KMT leadership had to devise strategies that can credibly commit to ordinary court independence, which would otherwise be reversed thereafter. This unique implication guides a qualitative empirical analysis that reinterprets the historical events surrounding the judicial reforms that took place in the mid-1990s. The results yield strong evidence in support of the theory.